2021
DOI: 10.3389/fmicb.2021.771292
|View full text |Cite
|
Sign up to set email alerts
|

The Evasion of Antiviral Innate Immunity by Chicken DNA Viruses

Abstract: The innate immune system constitutes the first line of host defense. Viruses have evolved multiple mechanisms to escape host immune surveillance, which has been explored extensively for human DNA viruses. There is growing evidence showing the interaction between avian DNA viruses and the host innate immune system. In this review, we will survey the present knowledge of chicken DNA viruses, then describe the functions of DNA sensors in avian innate immunity, and finally discuss recent progresses in chicken DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Altogether, this highlights the importance of utilizing enrichment techniques that are tailored to the environment of interest and the research questions being asked. Whether the purpose is to assign taxonomy [74], reveal mechanisms to avoid host defenses [75], identify auxiliary metabolic genes [76], or investigate mobile reservoirs for antimicrobial resistance genes [77,78], obtaining functional gene predictions is a critical step in analyses of viral communities. However, it can be quite challenging to assign functional predictions to viral genes annotated from metagenomic environmental data due to their large sequence diversity and the undercharacterization of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, this highlights the importance of utilizing enrichment techniques that are tailored to the environment of interest and the research questions being asked. Whether the purpose is to assign taxonomy [74], reveal mechanisms to avoid host defenses [75], identify auxiliary metabolic genes [76], or investigate mobile reservoirs for antimicrobial resistance genes [77,78], obtaining functional gene predictions is a critical step in analyses of viral communities. However, it can be quite challenging to assign functional predictions to viral genes annotated from metagenomic environmental data due to their large sequence diversity and the undercharacterization of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…ChTLR21was the most upregulated of all selected chTLRs in our study, and suggested it involved in the host recognition of early E. tenella infection. chTLR21 mainly recognises CpG oligodeoxynucleotides (CPG‐ODN) of pathogens and dimerises and recruits the adaptor factor MyD88, resulting in inflammatory cytokine secretion 32 . Zhang et al reported that chTLR21 was downregulated in the bursa while it upregulated in the Harderian gland when the chicken was infected with fowl adenovirus (FAdVs) 33 .…”
Section: Discussionmentioning
confidence: 99%
“…chTLR21 mainly recognises CpG oligodeoxynucleotides (CPG-ODN) of pathogens and dimerises and recruits the adaptor factor MyD88, resulting in inflammatory cytokine secretion. 32 Zhang et al reported that chTLR21 was downregulated in the bursa while it upregulated in the Harderian gland when the chicken was infected with fowl adenovirus (FAdVs). 33 Zhang et al reported…”
Section: Changes In Hdp Gene Expression In the Caecum Of E Tenella-in...mentioning
confidence: 99%
“…Phages are known to encode multiple proteins to counter bacterial defenses 20,25,26 . In most cases, each anti-defense phage protein inhibits only a narrow range of defense systems.…”
Section: Discussionmentioning
confidence: 99%